Drug-induced liver injuries in pregnancy in the context of polypragmasy - N. Yu. Velts; E. O. Zhuravleva; M. A. Darmostukova; K. E. Zatolochina; O. S. Alyautdina (Безопасность и риск фармакотерапии, 2018)
Pregnancy is characterized by overexertion of metabolism in the liver and some changes in metabolism, which can lead to various, including severe organ, damage. During pregnancy, according to international epidemiological studies, more than 80 % of women take medicines. Under polypragmasy it is extremely difficult to isolate a particular medicine responsible for the drug pathology in the liver in pregnant women. The article presents a retrospective analysis of spontaneous reports accepted from the Russian database of AIS Roszdravnadzor for the period from 01.01.2009 to 31.12.2016.